Efektivitas Manajemen Konflik Keluarga dalam Mediasi Untuk Mengurangi Tingkat Perceraian di Kabupaten Langkat (Studi Kasus Pengadilan Agama Stabat Kelas I B) - Mita Arianti; Azhar Azhar; Diyan Yusri (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Activities to minimize a problem or resolve conflicts in the family are a form of family conflict management that is always used in the mediation process at the Religious Court. Mediation is a way of resolving disputes through a negotiation process to obtain an agreement between the parties with the assistance of a mediator according to PERMA No. 1 of 2016. In this study, researchers used qualitative methods and field research with primary data sources, namely covering the results of interviews and observations at the Stabat Class I B Religious Court and secondary data sources from Perma No. 16 of 2016 as well as scientific papers relevant to the title of the researcher's thesis. Data collection techniques by means of direct interviews with judge or non-judge mediators in the Religious Court and documentation. The results showed that the application of family conflict management in mediation at the Stabat Religious Court has been maximally carried out, but because every case registered with the Religious Court is mostly a case that already has an agreement to divorce, the mediator as a third party in the peace process is only able to carry out his duties according to his authority, namely as a neutral party, the rest of all decisions are on the litigants. Therefore, it can be concluded that although family conflict management is always used in mediation, it is still unable to support mediation as an alternative in reducing divorce rates in Langkat Regency.